The Role of Adversity Quotient in Shaping Academic Resilience among Junior High School Students in Kisaran Timur - Elfira Rahmadani; Dian Armanto; Pardomuan Sitompul; Ely Syafitri (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the distribution and characteristics of the Adversity Quotient (AQ) among junior high school students in Kisaran Timur, Indonesia, within the framework of the Merdeka Curriculum, which emphasizes character education. AQ, based on Stoltz’s CORE model—Control, Ownership, Reach, and Endurance—reflects students' capacity to respond to academic and personal challenges. Regional data on AQ in semi-urban settings remain limited, hindering context-specific educational interventions. A quantitative descriptive approach was employed, involving 1,046 Grade VII students from four public junior high schools. Data were collected using a culturally adapted and validated version of the Adversity Response Profile questionnaire. AQ profiles were analyzed using descriptive statistics based on both categorical classification (Climber, Camper, Quitter) and CORE indicators. Findings revealed varying AQ profiles across schools. SMPN 7 had the highest percentage of Climbers (60%), while SMPN 3 had the highest percentage of Quitters (25%). Across all schools, Control and Endurance scores were relatively high, while Ownership and Reach were consistently lower, indicating weaker skills in accountability and limiting the impact of adversity. School-level factors—such as teaching style, peer support, and access to guidance—emerged as influential. The data highlight that student resilience is shaped not only by individual traits but also by the school environment. These findings support the integration of AQ data into targeted character education strategies. AQ-informed interventions such as mentoring, teacher training, and reflective practices can enhance students' resilience and support the goals of the Merdeka Curriculum.